Respuesta :
2x²-6x+8=0
x²-3x+4=0
D=b²-4ac=9-16=-7
x=(3+/-i√7)/2
correct answer is the last one
x²-3x+4=0
D=b²-4ac=9-16=-7
x=(3+/-i√7)/2
correct answer is the last one
Answer:
Option 4 - the quantity of 3 plus or minus i square root 7 all over 2
Step-by-step explanation:
Given : Expression [tex]2x^2-6x=-8[/tex]
To find : The solution of the expression ?
Solution :
Expression [tex]2x^2-6x=-8[/tex] can be written as
[tex]2x^2-6x+8=0[/tex]
[tex]x^2-3x+4=0[/tex]
Solve by quadratic formula,
The general form of quadratic equation is [tex]ax^2+bx+c=0[/tex] with solution [tex]x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
On comparing with [tex]x^2-3x+4=0[/tex], a=1 , b=-3, c=4
Substitute in solution,
[tex]x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
[tex]x=\frac{-(-3)\pm\sqrt{(-3)^2-4(1)(4)}}{2(1)}[/tex]
[tex]x=\frac{3\pm\sqrt{9-16}}{2}[/tex]
[tex]x=\frac{3\pm\sqrt{-7}}{2}[/tex]
[tex]x=\frac{3\pmi\sqrt{7}}{2}[/tex]
So, The solution is the quantity of 3 plus or minus i square root 7 all over 2.
Therefore, Option 4 is correct.